2013
DOI: 10.1089/thy.2012.0253
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Features of Thyroid Pyramidal Lobe, Accessory Thyroid, and Ectopic Thyroid as Assessed by Computed Tomography: A Multicenter Study

Abstract: Neck CT is useful for detecting the presence, size, configuration, and location of the pyramidal lobe and other thyroid variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 7 publications
3
30
5
1
Order By: Relevance
“…Thyroid variants, such as a TPL and lingual thyroid, have pre-contrast attenuation and enhancement pattern identical to the thyroid gland, which makes them easily identifiable on CT (10, 14, 15). Single- and multicenter studies have reported that TPLs are present in 41.3% (135/327) and 44.6% (981/2200) of study patients, respectively (9, 10). These results are similar to cadaveric or surgical studies, suggesting that neck CT is a feasible diagnostic tool for detecting TPLs and other thyroid variants in patients undergoing total thyroidectomy (1, 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid variants, such as a TPL and lingual thyroid, have pre-contrast attenuation and enhancement pattern identical to the thyroid gland, which makes them easily identifiable on CT (10, 14, 15). Single- and multicenter studies have reported that TPLs are present in 41.3% (135/327) and 44.6% (981/2200) of study patients, respectively (9, 10). These results are similar to cadaveric or surgical studies, suggesting that neck CT is a feasible diagnostic tool for detecting TPLs and other thyroid variants in patients undergoing total thyroidectomy (1, 8).…”
Section: Resultsmentioning
confidence: 99%
“…Available preoperative methods for detecting TPL include scintigraphy, ultrasonography (US), and computed tomography (CT) (4, 9, 10, 11, 12). Scintigraphic detection of a TPL depends on the specific thyroid disorder and the experience of the operator (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPL appears to be related to the distal portion of the thyroglossal duct, an embryological structure, which initially develops along the migratory path of the thyroid gland and usually disappears during later development [3]. Most autopsy- or surgery-based studies have reported that a TPL is present in more than 50% of the general population [1-3], but a study using computed tomography has demonstrated that the prevalence of TPL is 44.6% in South Korea [10]. To date, no USbased studies of TPL prevalence have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Its course is usually upwards, lying in midline or laterally depending on its attachment with thyroid gland which may be form superior border of the isthmus, medial or superior aspects of either of thyroid lobes [5]. In literature, pyramidal lobe was most frequently observed to be originated from left lobe as compared to right lobe and isthmus, with frequency of 15% to 75% as per anatomy books [6][7][8]. In cadaver studies, the prevalence of pyramidal lobe reported, ranges from 28.9% -55% [1].…”
Section: Discussionmentioning
confidence: 99%